Advances in research on fat infiltration and lumbar intervertebral disc degeneration - Wang, Zairan; Zhao, Zijun; Han, Shiyuan; Hu, Xianghui; Ye, Liguo; Li, Yongning; Gao, Jun (Frontiers in Endocrinology, 2022)
Low back pain (LBP) is a disabling condition with no available cure, severely affecting patients' quality of life. Intervertebral disc degeneration (IVDD) is the leading cause of chronic low back pain (CLBP). IVDD is a common and recurrent condition in spine surgery. Disc degeneration is closely associated with intervertebral disc inflammation. The intervertebral disc is an avascular tissue in the human body. Transitioning from hematopoietic bone marrow to bone marrow fat may initiate an inflammatory response as we age, resulting in bone marrow lesions in vertebrae. In addition, the development of LBP is closely associated with spinal stability imbalance. An excellent functional state of paraspinal muscles (PSMs) plays a vital role in maintaining spinal stability. Studies have shown that the diminished function of PSMs is mainly associated with increased fat content, but whether the fat content of PSMs is related to the degree of disc degeneration is still under study. Given the vital role of PSMs lesions in CLBP, it is crucial to elucidate the interaction between PSMs changes and CLBP. Therefore, this article reviews the advances in the relationship and the underlying mechanisms between IVDD and PSMs fatty infiltration in patients with CLBP.